PEDAGOGICAL OPPORTUNITIES FOR DEVELOPING STUDENTS’ SPIRITUAL AND MORAL COMPETENCIES BASED ON NATIONAL VALUES AND TRADITIONS (Eureka Journal of Education & Learning Technologies, 2026)
In the context of educational modernization and globalization, the preservation of national identity and the development of students' spiritual and moral competencies have become fundamental priorities of educational policy. National values, customs, and traditions represent an essential educational resource for fostering ethical behavior, social responsibility, patriotism, and cultural awareness among young people. This article explores the pedagogical opportunities for developing students' spiritual and moral competencies through the integration of national values into the educational process. The study employs theoretical analysis, comparative pedagogy, and content analysis to investigate the role of value-oriented education in shaping students' personalities. The findings demonstrate that educational activities based on cultural heritage significantly contribute to moral maturity, civic engagement, emotional intelligence, and social adaptation. The article concludes that combining traditional values with innovative pedagogical technologies creates an effective educational model capable of preparing morally responsible and socially active citizens.
Keywords: national values, spiritual competence, moral competence, pedagogy, traditions, cultural heritage, value education, personality development, citizenship education, ethical education.